The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5799/ahinjs.02.2013.03.0092
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori genotypes among patients in a university hospital in Egypt: identifying the determinants of disease severity

Abstract: Objective: To detect the various of H. pylori genotypes, determine the most prevalent one, and to identify the determinants of disease severity. Methods:Biopsies from 90 patients were collected, however 69 were exclusively analyzed. Recognition of H. pylori was made by rapid urease test, histopathology and polymerase chain reaction. The latter was used to amplify genes encoding for virulence markers such as CagA, vacAs1 and vacAs2.Results: cagA was identified in 45 isolates (65.2%), vacAs1 in 54 (78.3%, predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
6
13
2
Order By: Relevance
“…Our results revealed m2 as the main allele that similar to studies from Iraq, Turkey, Iran, Saudi Arabia, and the middle east region characterized m2 as the main allele [14,32,33,[39][40][41][42]. In another hand, some studies reported that the predominant vacA m subtype was m2 and no association or no role between vacA m genotypes and the development of peptic ulcer [2,32,33,42,43], whereas other studies had been found that vacA m1 strains are associated with high levels of inflammation in the gastric mucosa and increased the risk of gastric atrophy and carcinoma [2,44]. However, the results were different from country to others, but we consistent with different studies those of Middle Eastern countries, in which the vacA s1 and m2 subtypes have been predominant subtypes [32,42,45,46].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our results revealed m2 as the main allele that similar to studies from Iraq, Turkey, Iran, Saudi Arabia, and the middle east region characterized m2 as the main allele [14,32,33,[39][40][41][42]. In another hand, some studies reported that the predominant vacA m subtype was m2 and no association or no role between vacA m genotypes and the development of peptic ulcer [2,32,33,42,43], whereas other studies had been found that vacA m1 strains are associated with high levels of inflammation in the gastric mucosa and increased the risk of gastric atrophy and carcinoma [2,44]. However, the results were different from country to others, but we consistent with different studies those of Middle Eastern countries, in which the vacA s1 and m2 subtypes have been predominant subtypes [32,42,45,46].…”
Section: Resultssupporting
confidence: 90%
“…The strains in the present study belong to western type, as studies indicated s1b subtype is rarely found in East-Asian countries [29,32,38]. Our results revealed m2 as the main allele that similar to studies from Iraq, Turkey, Iran, Saudi Arabia, and the middle east region characterized m2 as the main allele [14,32,33,[39][40][41][42]. In another hand, some studies reported that the predominant vacA m subtype was m2 and no association or no role between vacA m genotypes and the development of peptic ulcer [2,32,33,42,43], whereas other studies had been found that vacA m1 strains are associated with high levels of inflammation in the gastric mucosa and increased the risk of gastric atrophy and carcinoma [2,44].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous studies in Turkey, Iraq, Iran, Saudi Arabia (Hussein, 2010) and China (Chung et al, 2010), m2 was predominantly found in all studied H. pylori strains (70%) previously reported. However, this was inconsistent with previous results obtained from Egypt where equal distribution of vacA m1 and m2 was found (Amer et al, 2013). Genetic variation within virulence factors may account for differences in the pathogenic properties of strains, and thus may help to explain the discrepancies between the number of infected individuals and those that end up developing gastric cancer (Ferreira et al, 2014).…”
Section: Discussioncontrasting
confidence: 76%
“…This similarity in H. pylori genotypes in three neighboring countries, Egypt, Jordan, and Gaza strip, indicates a geographic influence, which was reported by Abu Amra (2010). Whereas in Egypt, Amer et al (2013), reported that all possible combination of vacA s1 with m were recognized in their work, in addition, H. pylori virulence could not be predicted in relation to different genotypes.…”
Section: Discussionmentioning
confidence: 87%